Principal's Leadership Strategy In Improving Teacher Performance At State Senior High School 1 Singkep Lingga Regency, Riau Islands Province: english - Lexminander; Tety Kurmalasari; Nevrita; Dody Irawan; Zaitun; Encik Abdulhajar (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
This study aims to analyze the principal's leadership strategy in improving teacher performance at Singkep 1 State Senior High School, specifically through strengthening teachers' pedagogical, professional, social, and personality competencies. The research approach used is descriptive qualitative with data collection techniques through observation, interviews, and documentation studies. The results show that the principal applies transformational and collaborative leadership strategies, including competency improvement program planning, academic supervision, motivation, and strengthening work culture and teacher discipline. Pedagogical competency improvement is carried out through classroom supervision, lesson study, and training on learning tools; professional competency through workshops, MGMP, and scientific publications; social competency through collaboration between teachers and partnerships with the community; and personal competency through character development, role models, and professional ethics. The impact of these strategies is an increase in the quality of learning, work discipline, and teachers' ability to develop learning tools, as well as contributing to improving school accreditation. In conclusion, the principal has a strategic role in improving teacher performance through a structured, sustainable, and measurable competency improvement program.